A relação Palavra-Espírito Santo na Constituição Dogmática Dei Verbum do Concílio Vaticano II - Felix, Elcio Rubens Mota (2013)
This assignment aims to verify the relation between the Word and the Spirit in the Dei Verbum Dogmatic Constitution, of Vatican Council II. Therefore, we are going to analyze, at first, this Constitution, placing it in the Vatican Council II. It is in it that the Dei Verbum is elaborated. After, we are going to focus our research based on the analysis of the text from the Dei Verbum; we are going to strictly focus our research in the references that are done in it about the Spirit. In this way, our investigation, which is predominantly bibliographical, tries to show that, although there are few references about the Spirit in that document, when you read it, it is possible to characterize or identify the ways of relation between the Word and the Spirit. And even more if this reading is taken into account, as it is our purpose, that the Dei Verbum is essentially a document aimed to present a doctrine about God s Word revelation. We also verify that this doctrine has among its presumptions that the relation between the Word and the Spirit will cause the human s listening to the Word, conducting him to give an answer, which is also to look for listening it. From the genuine listening of God s Word which is revealed into the Spirit, and the man offers to do, they may depend on all the other ways of revelation in which the human being involves himself: the relation with himself, the relation with the others, the relation with the world, with the society and even the relation with the things. From the authentic man s ability of listening God s Word can depend on a new way of man s being and living in this world. Something that the Council has already said, namely it was presupposed in its deliberations. The Council spirit essentially proposed the society s updating relation, with the world and the science. And definitely it is the listening that could give the outlines of this relation